A comparative analysis on safety culture in domestic and foreign health care facilities and enterprises of other activities (message 2) - Yavorovsky , A.P.; Rygan, M.M.; Naumenko , A.N.; Skaletsky, Yu.N.; Gichka , S.G.; Ivanko, A.V.; Varyvonchyk , D.V.; Shkurba, A.V.; Bugro, V.I.; Brukhno , R.P.; Zinchenko, T.О.; Gorval , A.K.; et al. (Medicni Perspektivi, 2021)
The characteristics of the safety culture of patients and personnel in health care facilities in Ukraine as a whole and separately among doctors-pathologists are analyzed with correlation of the data obtained with similar indicators of the culture of patient safety in medical facilities of other countries and comparison with the safety culture of workers of domestic nuclear power plants. It was confirmed that the weaknesses of the safety culture of the personnel of domestic hospitals is characterized by "Reaction to mistakes", which indicates the prevalence of the culture of blame (unfair culture) in domestic hospitals and, as a result, the absence of real data on medical errors and other incidents of patient safety. The high percentage of positive responses to the safety culture characteristic “Response to mistakes” among the workers of Ukrainian nuclear power plants is an example of the possibility of forming an appropriate safety culture in a separate domestic industry, and the high percentage of positive answers by this characteristic in domestic pathologists is a significant potential for the development of a safe hospital environment for patients. in Ukraine.